IMMUNOHISTOCHEMICAL STUDY OF M1 AND M2 MACROPHAGES IN BREAST CANCER WITH MICROCALCIFICATIONS - Kolomiiets, Olena; Moskalenko, Roman (Eastern Ukrainian Medical Journal, 2023)
Introduction. Breast cancer (BC) is a significant medical and social problem, as it is the leading cause of cancer-related mortality in women worldwide. Microcalcifications in the breast tissue are essential in developing the pathological process and affect the prognosis and metastasis. The tumor microenvironment consists of cancer cells and stromal cells such as fibroblasts, endothelial cells, pericytes, and immune cells, including M1 and M2 macrophages.The work aims to study the influence of microcalcifications on the polarization of macrophages in the tumor microenvironment of BC.Materials and methods. The study was conducted on 60 samples of BC, divided into 30 samples of BC with microcalcifications (group I) and a control group of 30 samples of BC without calcifications (group II). All microcalcifications met the criterion of size up to ≤1 mm. To study the pathohistological changes, BC's tissue was analyzed using macroscopic description, histology, and immunohistochemical study with antibodies against CD68 and CD163.Results. According to the results of an immunohistochemical study, it was found that the expression of CD68-positive macrophages of the M1 type is significantly higher in the tissue of samples of BC with microcalcifications, compared to samples of the control group (60.85 ± 2.71 cells in the field of view vs. 51.14 ± 2.89, p < 0.05). On the other hand, it was established that the average value of CD163 expression in group I was 53.21 ± 3.05 against 65.57 ± 3.75 (p ˂ 0.05) cells in the group of BC without calcification. Nevertheless, the localization of M1 and M2 macrophages in the tumor had standard features and did not differ.A possible mechanism of the effect of microcalcifications on the polarization of macrophages is their support of chronic inflammation in cancer tissues and, thus, the development of pro-inflammatory M1 phenotype in macrophages. Further studies are needed to obtain more unambiguous conclusions.